Study of situation awareness of cultural security based on social media analysis. (January 2020) - Li, Jianjun; Dai, Yonghui; Shi, Qinghua; Xian, Jin
With the intercultural exchanges between different countries becoming more and more frequent, the degree of cultural exchanges is gradually deepening, which brings more and more cultural security problems. As an important part of national security, cultural security is closely related to national interests. This article takes Chinese college students and social workers who just graduated as research objects, takes online comments on "hip-hop" culture and "funeral culture" as research objects, and uses literature research and empirical research methods to analyze social media comments and study the cultural security situation in China. It is concluded that online comments have a significant impact on cultural identity and cultural security, and negative online comments have a greater impact on both than positive online comments. In addition, cultural identity has a significant impact on cultural security. At the same time, the impact of cultural identity on online comments and cultural security is partly mediated. The results of this study will help to provide reference and guidance for the maintenance of cultural security.